Children’s Moral Education within the Family (A Case Study of Muhammadiyah Families in Sungai Pandan District, Hulu Sungai Utara Regency) - Ubaidillah Ubaidillah; Rahmad Hulbat (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Children's moral education in the family is an important part in the formation of children's character and behavior from an early age. The family is the first environment for children to receive education, especially moral education related to attitudes, behavior, and Islamic values ​​in everyday life. Muhammadiyah families pay attention to the development of children's morals through the habit of worship, role models, advice, and supervision within the family environment. This study aims to determine the moral education of children in Muhammadiyah families in Sungai Pandan District, Hulu Sungai Utara Regency. This study uses a field research type with a qualitative approach and case study method. The research subjects consisted of parents and children in Muhammadiyah families in Sungai Pandan District, Hulu Sungai Utara Regency. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were analyzed through the stages of editing, classification, data interpretation, and data presentation, while data validity was carried out through triangulation. The results of the study indicate that children's moral education in Muhammadiyah families in Sungai Pandan District, Hulu Sungai Utara Regency is carried out through the habit of worship, parental role models, giving advice, and supervision in everyday life. Parents play a crucial role in shaping children's behavior by instilling politeness, discipline, respect for others, and participating in religious activities. Consistently implemented moral education has a positive impact on children's behavioral development, despite challenges such as the influence of gadgets, social environments, and limited parental time to accompany their children